Characteristics and Infection Mechanism of Ganoderma Boninense in Oil Palm - Rossa Yunita; Azis Natawijaya (Research Perspective on Biological Science Vol. 4, 2025)
Ganoderma boninense is the primary causal agent of Basal Stem Rot (BSR) disease in oil palm. Understanding the interaction between the pathogen and the host is crucial for effectively managing BSR. The purpose of this paper is to provide a general overview of the characteristics and infection mechanism of G. boninense in oil palm plants. The infection process begins with the release of basidiospores from the basidiocarp, which then leads to the formation of dikaryotic mycelium. This dikaryotic mycelium undergoes hyphal morphogenesis to form needle-like structures that facilitate penetration into host cells. Infection in oil palm trees manifests through the formation of basidiocarps at the basal stem of the infected plant.